Asynchronous Video Feedback as a Game-Changer for Online Speaking Classes - Sabila, Arinas; Cahyono, Bambang Yudi; Anugerahwati, Mirjam (Universitas Hamzanwadi, 2024)
Asynchronous Video Feedback (AVF) allows students to replay or slow down video feedback for better comprehension, enabling them to thoroughly process and address issues, thereby enhancing their observational and reasoning skills. This study investigates the effectiveness and student perceptions of AVF in improving speaking skills in online English courses. Conducted in an online English course in Pare, Kediri, Indonesia, the research employed a mixed-methods design, including pretests, post-tests, surveys, and semi-structured interviews with eight participants from an online speaking class. The results revealed substantial improvements in learning outcomes, with the pretest mean score of 64.88 increasing to a posttest mean score of 84.88, indicating a significant enhancement in students' speaking capabilities. The study showed that AVF significantly improved pronunciation, grammar, vocabulary, and fluency. Additionally, AVF promotes self-directed learning and discipline, though a student's educational background may influence their comprehension, particularly concerning grammar. Compared to in-class feedback, AVF reduces feelings of embarrassment and fear, offering valuable insights for future online English classes. Therefore, AVF is proposed as an effective tool for developing students' speaking abilities in online courses.